Implementation Practices of Public Procurement Plans and Policies - Jacob, Jufri (JEJAK: Jurnal Ekonomi dan Kebijakan, 2017)
Public procurement issues have drawn many concerns and became a public debate because the rules and regulations are constantly reformed and restructured. Public procurement contributions in the world economy are very significant. In Indonesia, according to the Ministry of Finance, public procurement spending for 2009 was 33.4 percent of total government spending. This study aims to determine implementation practices of Public Procurement Plans or Rencana Umum Pengadaan (RUP) in Bitung City. The multiple statistical regression equation is used to process data from 47 respondents from regional apparatus task forces (SKPD) and the results show that the influence of independent variables (X) on dependent variable (Y) is 87.3 percent (R2), while 12.7 percent is influenced by other factors. The result of F-test shows 36.231> F- tableÂ  3.21. The calculated probability value is 0.000 which is smaller than 0.05. The partial test (t-test) from 9 independent variables (X) identifies 7 variables that have significant effects on the scores of RUP implementation (Y). The overall results of t-test show that the implementation practices of public procurement plans have significant effects of the higher compliance rates on the output of goods and services.